Family firms and labor market regulation - BENNEDSEN, Morten (Institutional Knowledge at Singapore Management University, 2014)
We investigate whether labor market regulation affects the performance difference between family and non-family firms across a large panel of more than 6,900 firms in 28 countries over 10 years. We establish two main results: family firms have a performance advantage over non-family firms in countries with less regulated labor markets, and the performance advantage of being family-controlled in countries with lower regulation is less pronounced in industries with high labor intensity and high labor volatility. These results are robust to matching and using a survey-based instrument for family control. Our results suggest that family control and labor market regulation to some extent are substitute governance mechanisms.